Liberación directa de puntos gatillos en el dolor miofascial cervical del adulto - Mónica Natali, Centeno Tayupanta (2020)
The research was developed in the modality of bibliographic review, the same that aimed to investigate through the different databases the effect that myofascial release produces in trigger points during the treatment of neck pain in adults in order to help immediate recovery, inhibiting the symptoms caused by said pathology and thus improving the quality of life of patients. During the review, it was possible to find 112 scientific articles that, through the evaluation and exclusion criteria according to the PEDro scale, were suppressed or admitted and the 35 articles that presented the highest score were taken into account through the flow diagram. giving them validity to be included in the research, they met with an assessment equal to or greater than 6 according to the scale; These articles were found in different languages such as Spanish and English, which provided information that helped to certify the immediate effect that myofascial release of trigger points produces in patients suffering from neck pain. The databases that were used in the compilation of the different articles for the preparation of this research were: PEDro, Enfispo, PubMed, Ciencie Direct, Cochrane library, Scopus, ProQuest, E-book and university repositories. The selected articles were from 2011 to the present year. At the conclusion of the research after the authors' discussion, it was possible to verify the efficacy of the myofascial trigger point release technique in patients with cervical pain, so it is recommended to continue with this type of study as it will help improve quality of life of patients suffering from this pathology.